Analisis Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Karyawan Pada PT Pash Mitra Mandiri - Umar Usman; Adinda Tri Wahyuni (Mulia Pratama, 2021)
The competition between firms is becoming more fierce along with the expansion of economic growth in the trade sector, particularly with the rise of new types of retail businesses. How do Quick Ratio, Inventory Turnover, and Debt to Assets Ratio Affect Return on Equity in Retail Trading Sub Sector Companies on the Indonesia Stock Exchange? is how the problem in this study is formulated. The financial reports of companies in the retail trade sub-sector that are listed on the IDX served as the study's primary source of secondary data. Multiple regression analysis and hypothesis testing (F test and t test) are the data analytic methods employed in this study. Based on calculations using multiple regression analysis, the result is Y = - 4.170 + 0.087QR + 4.291ITO -0.424DAR, a constant of -4.170 means that if the Quick Ratio, Inventory Turnover, and Debt to Assets Ratio value is 0 then the Return on Equity value is -4.170 . Partially the Quick Ratio has no positive and insignificant effect on Return On Equity as indicated by tcount 1.839 < ttable 2.021. Inventory Turnover has a positive and significant effect on Return On Equity which is indicated by tcount 2.760 > ttable 2.021 and the Debt to Assets Ratio has a negative and significant effect on Return On Equity which is indicated by tcount -2.076 < ttable 2.02. And simultaneously the Quick Ratio, Inventory Turnover, Debt to Assets Ratio has a significant effect on Return On Equity as indicated by tcount 5.587 > ttable 2.84. In conclusion, the company is expected to be able to increase the value of the company and be taken into consideration in evaluating financial performance in the future, for investors it is expected to be a consideration in determining investment, and for further researchers it is recommended to add other indicators that are different from this research.